2000
DOI: 10.1007/bf02682267
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of asymmetry of rat brain nuclei under normal conditions and during exposure to microgravitation

Abstract: Histological and morphometrical analysis of the brain and peripheral analyzers revealed proliferative migration abnormalities of brain development and neuron differentiation in mammals during a space flight, which can limit space exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Proshchina and Savel'ev (1998) showed that in R. temporaria the right brain hemisphere had a larger volume of grey matter, but this asymmetry disappears between the stages 27-36 (Dabagyan & Sleptsova, 1975). It is known that a significant preference to turn to the right in a T-maze exists in rats and mice only during a certain period of life, namely between 11 and 19 months after birth (Obukhova , Klimenko, & Solov'eva, 1997;Solov'eva & Obukhova, 2001).…”
Section: Turning Bias In Tadpoles and Behavioural Asymmetries In Adultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Proshchina and Savel'ev (1998) showed that in R. temporaria the right brain hemisphere had a larger volume of grey matter, but this asymmetry disappears between the stages 27-36 (Dabagyan & Sleptsova, 1975). It is known that a significant preference to turn to the right in a T-maze exists in rats and mice only during a certain period of life, namely between 11 and 19 months after birth (Obukhova , Klimenko, & Solov'eva, 1997;Solov'eva & Obukhova, 2001).…”
Section: Turning Bias In Tadpoles and Behavioural Asymmetries In Adultsmentioning
confidence: 93%
“…Nevertheless a few examples can be considered. Proshchina and Savel'ev (1998) studied turning behaviour of tadpoles and found no turning preference in B. bufo when they swam out of a T-maze in a current of water. These data do not make a bridge between the behavioural handedness in adult B. bufo (Bisazza et al, 1996(Bisazza et al, , 1997 and its tadpoles (Proshchina & Savel'ev, 1998).…”
Section: Turning Bias In Tadpoles and Behavioural Asymmetries In Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to published data, alterations in many gene activation and gene pathway changes and those associated with the influence of spaceflight conditions have been identified [57]. Moreover, microgravity, and possibly other nonspecific effects of spaceflight, can alter normal brain development [58]. There are also data showing that space-relevant radiation may induce changes in neuronal functions.…”
Section: Gecko Brain In Prolonged Spaceflight Experimentsmentioning
confidence: 99%